2012
DOI: 10.1262/jrd.11-005s
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Changes in Immunoreactivity of Activin Signaling Component Proteins in Wild Ground Squirrel Testes

Abstract: Abstract. The seasonal spermatogenesis and localization of inhibin/activin subunits (alpha, betaA, betaB) in the testes of wild ground squirrel has been previously described; however, the expression pattern of activin receptors and cytoplasmic signaling SMADs has not been detected in any seasonal breeders. The objective of this study was to investigate the abundance and cellular localization of activin signaling components in testes of the wild ground squirrel during the breeding and nonbreeding seasons. The i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…The background of each section in the different periods was used as the internal control during evaluation of the intensity of the immunostaining. Similar to our previous studies [21,22], immunoreactivity was shown as -for negative staining, + for the positive staining, ++ for the strongly positive staining and +++ for very strongly positive staining. …”
supporting
confidence: 88%
“…The background of each section in the different periods was used as the internal control during evaluation of the intensity of the immunostaining. Similar to our previous studies [21,22], immunoreactivity was shown as -for negative staining, + for the positive staining, ++ for the strongly positive staining and +++ for very strongly positive staining. …”
supporting
confidence: 88%
“…Forty-six wild male ground squirrels (twenty six in the breeding season and twenty in the nonbreeding season) that were thought to be adults based on their body weights (general standard range of body weight for adult squirrel: 242–412 g) were captured in April to September (breeding season, April and May; nonbreeding season, June to September) of 2007 in Hebei Province, China [22, 23]. After anesthesia, all animals were euthanized by decapitation.…”
Section: Methodsmentioning
confidence: 99%
“…The testis and epididymis of this species exhibits distinct seasonal morphology changes from the breeding season to the nonbreeding season [21,22,23,24]. Our published results have indicated that seasonal changes in the distribution of inhibin/activin α, β A and β B subunits and activin signaling proteins were accompanied by changes in testicular activity in male ground squirrels and other mammals [21, 22, 25,26,27,28,29]. However, little is known about the role of inhibin/activin subunits in the epididymal tissue of this wild species.…”
mentioning
confidence: 99%
“…From June to March, however, was the time of hibernation, or the nonbreeding season, in which the wild ground squirrel went through a long period of sexual dormancy [18-20]. The wild female ground squirrel provided us with a useful model to study the role of androgen in follicular development during the breeding and nonbreeding seasons.…”
Section: Introductionmentioning
confidence: 99%